An Approach for Automating Use Case Refactoring - Rago, Alejandro Miguel (2014)
Carrying out requirements capture and modeling activities successfully is not easy, often requiring a thoughtful analysis of clients needs and demanding an adequate expertise from analysts. To ensure a fluid communication among stakeholders, analysts must take advantage of modeling techniques while describing requirements and exploit reuse and abstraction practices so as to avoid redundancy (for instance, using relations between use cases). Unfortunately, these practices are seldom applied because inspecting requirements such as textual use cases by hand, looking out for faulty or duplicate functionalities, is a challenging and error-prone activity. In this context, we introduce an assistive approach called ReUse that searches redundancy eficiencies in use case specifications and allows to fix them with relation-based refactorings. Our approach makes use of text processing and sequence alignment techniques to discover deficiencies (e.g., duplicate functionality). We have evaluated ReUse in five case studies, achieving promising results.